Pengembangan Multimedia Interaktif untuk Meningkatkan Keterampilan Berpikir Kreatif Mahasiswa pada Materi Larutan Penyangga - Ratna Azizah Mashami (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2016)
Learning sources which served macroscopic, submicroscopic, and symbol level in one unity weren’t suitable yet. Whereas those learning sources very needed in order chemistry concept which still abstract could be understood by students. This research aimed to develop interactive multimedia with macroscopic, submicroscopic, and symbol approach on buffer material. This research was Research and Development. Procedure of developing product consisted of five stages, namely analysis, design, develop, implementation, and evaluation. On implementation stage was conducted try out effect of interactive multimedia toward students’ creative thinking skills. The data of creative thinking was gotten from essay test and analyzed used score of N-gain. Result of research showed that interactive multimedia was proper used and could improve students’ creative thinking skills with mean score of N-gain was 73,74% (high category).